Religious Studies and the Production of Critical Religious Moderation: Epistemic Humility and Reflexive Habitus in Indonesian Higher Education - Aslam Sa'ad; Muhammad Faiz; Muhammad Masruri (UIN Sunan Gunung Djati Bandung, 2025)
This study analyzes the relationship between Religious Studies and the discourse of religious moderation in Indonesian higher education by challenging the dominant view that positions religious moderation primarily as a state-driven normative agenda or a mechanism for transmitting moral values. The purpose of this research is to explain how Religious Studies operates as an epistemic space that shapes intellectual dispositions for managing religious diversity, rather than as an instrument of normative harmonization. This study employs a qualitative approach, using in-depth interviews and focus group discussions (FGDs) with lecturers and students at Universitas Islam Negeri Sunan Kalijaga and Universitas Gadjah Mada, complemented by an analysis of curricular documents and institutional practices. The findings reveal three main results. First, Religious Studies systematically produces epistemic humility, enabling subjects to recognize the limits of truth claims without falling into relativism. Second, through the repetition of academic practices, a reflexive habitus emerges that shifts religious engagement from identity defense toward argumentative reasoning. Third, Religious Studies equips subjects with the capacity to manage tensions among religion, culture, and nationalism critically and contextually. This study offers an original contribution by proposing the concept of critical religious moderation as an intellectual-ethical capacity produced through scholarly practice. The implications of this research underscore the importance of protecting epistemic autonomy and strengthening reflective educational ecosystems within policies on religious moderation in higher education.